Modulatory effects of traditional Chinese medicine and derived active metabolites on autoimmune-inflammatory signaling pathways in multiple sclerosis: a narrative review - Die Qian; Xiaohong Li; Jingjing Ge; Shuai Liu; Mingmin Na; Maokui Huang; Qingyan Mo; Mingqian Ju; Chunping Wan (Frontiers in Pharmacology, 2026)
Multiple sclerosis (MS), an immune-mediated neuroinflammatory disease, is characterized by demyelination, axonal injury and extensive destruction of the integrity of the central nervous system. Experimental autoimmune encephalomyelitis (EAE) is the most commonly used model for simulating the pathological features of human MS. Presently, there is still much room for improvement in the treatment strategy of MS. More and more studies have shown that traditional Chinese medicine (TCM) and related active metabolites are beneficial to the treatment of MS, and skillfully regulate the levels of inflammatory factors and immune system imbalance. Focusing on the core pathological mechanisms of MS, this review elucidates the beneficial effects of TCM in the prevention and treatment of MS via the modulation of autoimmune responses and inflammation-associated signaling pathways, as well as the underlying mechanisms of action. The main keywords “multiple sclerosis”, “experimental autoimmune encephalomyelitis”, “traditional Chinese medicine”, “natural metabolites”, “bioactive metabolites”, “autoimmune”, “inflammatory signals” and other details were retrieved from PubMed and Web of Science, Scopus, ScienceDirect, and Google Scholar. The results indicate that TCM preparations, including botanical drugs, active metabolite monomers and formulas, exert neuroimmunomodulatory effects via modulating Th1/Th2 and Th17/Treg cell balance and the CXCR6/CXCL16 signaling axis, and consequently inhibit excessive immune activation. Additionally, it regulates a variety of inflammation related signaling pathways, including NLRP3, TLR4/MyD88/NF-κB, MAPK, PI3K/Akt and JAK/STAT signal pathways, thus contributing to the treatment of MS. This study deepens our understanding of the mechanisms of TCM intervention in MS, and opens up a new perspective for clarifying the clinical value and development prospect of TCM in the treatment of MS.